2016
DOI: 10.18632/oncotarget.13202
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum granulocyte-macrophage colony-stimulating factor levels during radiotherapy predict favorable outcomes in lung and esophageal cancer

Abstract: The combination of exogenous granulocyte-macrophage colony-stimulating factor (GM-CSF) with radiotherapy (RT) has been demonstrated to strengthen the antitumor immune response. We hypothesized that the variation of GM-CSF during RT was correlated with cancer prognosis. We measured serum levels of GM-CSF and interferon-γ (IFN-γ) before and during RT in 126 unresectable lung and esophageal cancer patients and performed survival analyses. Upregulated GM-CSF levels during RT correlated with longer overall survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Recent studies have shown that GM-CSF has a much broader range of biological activities and exerts antitumor effects on cancer patients in an immune-dependent and -independent manner. A previous publication by our group showed that increased serum GM-CSF levels during radiotherapy were associated with better survival, which indicated the potential antitumor effects of GM-CSF, although the exact mechanism was unclear 22. Many other studies of pancreatic ductal adenocarcinoma have also provided supporting evidence for the antitumor effects of GM-CSF.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Recent studies have shown that GM-CSF has a much broader range of biological activities and exerts antitumor effects on cancer patients in an immune-dependent and -independent manner. A previous publication by our group showed that increased serum GM-CSF levels during radiotherapy were associated with better survival, which indicated the potential antitumor effects of GM-CSF, although the exact mechanism was unclear 22. Many other studies of pancreatic ductal adenocarcinoma have also provided supporting evidence for the antitumor effects of GM-CSF.…”
Section: Discussionmentioning
confidence: 78%
“…A previous publication by our group showed that increased serum GM-CSF levels during radiotherapy were associated with better survival, which indicated the potential antitumor effects of GM-CSF, although the exact mechanism was unclear. 22 Many other studies of pancreatic ductal adenocarcinoma have also provided supporting evidence for the antitumor effects of GM-CSF. Urdinguio et al 23 discovered that the 5-year survival rates were high in colon cancer patients overexpressing GM-CSF and their receptors.…”
Section: Discussionmentioning
confidence: 89%
“…A prospective clinical trial verifies that metastatic solid tumors treated with both radiotherapy and GM-CSF tend to experience tumor shrinkage ( 17 ). The increase in GM-CSF levels during radiotherapy correlates with longer PFS and OS in lung and esophageal cancer patients, indicating its potential as a prognostic biomarker ( 44 ). As distinct stages in triggering the immune response, radiotherapy, immunotherapy, and GM-CSF have the potential to enhance the efficacy against cancerous growths to different extents.…”
Section: Discussionmentioning
confidence: 99%